Controlled carrier screening in p-n NiO/GaN piezoelectric generators by an Al2O3 insertion layer. (10th November 2017) - Johar, Muhammad Ali; Jeong, Dae Kyung; Hassan, Mostafa Afifi; Kang, Jin-Ho; Ha, Jun-Seok; Lee, June Key; Ryu, Sang-Wan
Abstract: The performance of a piezoelectric generator (PG) depends significantly on the internal screening process inside the device. As piezoelectric charges appear on both ends of the piezoelectric crystal, internal screening starts to decrease the piezoelectric bias. Therefore, the piezoelectric energy generated by external stress is not fully utilized by external circuit, which is the most challenging aspect of high-efficiency PGs. In this work, the internal screening effect of a NiO/GaN p-n PG was analyzed and controlled with an Al2 O3 insertion layer. Internal screening in the p-n diode PG was categorized into free-carrier screening in neutral regions and junction screening due to charge drift across the junction. It was observed that junction screening could be significantly suppressed by inserting an Al2 O3 layer and that effect was dominant in a leaky diode PG. With this implementation, the piezoelectric bias of the NiO/GaN PG was improved by a factor of ~100 for high-leakage diodes and a factor of ~1.6 for low-leakage diodes. Consequently, NiO/Al2 O3 /GaN PGs under a stress of 5 MPa provided a piezoelectric bias of 12.1 V and a current density of 2.25 µ A cm −2 . The incorporation of a highly resistive Al2 O3 layer between p-NiO and n-GaN layers in NiO/GaN heterojunctions provides an efficient means of improving the piezoelectric performance by controlling the internal screening of the piezoelectric field.